An Outdated Notion of Antibody Specificity is One of the Major Detrimental Assumptions of the Structure-Based Reverse Vaccinology Paradigm, Which Prevented It from Helping to Develop an Effective HIV-1 Vaccine - Van Regenmortel, Marc H. V. (Frontiers in Immunology, 2014)
The importance of paradigms for guiding scientific research is explained with reference to the seminal work of Karl Popper and Thomas Kuhn. A prevalent paradigm, followed for more than a decade in HIV-1 vaccine research, which gave rise to the strategy known as structure-based reverse vaccinology is described in detail. Several reasons why this paradigm did not allow the development of an effective HIV-1 vaccine are analyzed. A major reason is the belief shared by many vaccinologists that antibodies possess a narrow specificity for a single epitope and are not polyspecific for a diverse group of potential epitopes. When this belief is abandoned, it becomes obvious that the one particular epitope structure observed during the crystallographic analysis of a neutralizing antibody-antigen complex does not necessarily reveal which immunogenic structure should be used to elicit the same type of neutralizing antibody. In the physical sciences, scientific explanations are usually presented as logical deductions derived from a relevant law of nature together with certain initial conditions. In immunology, causal explanations in terms of a single cause acting according to a law of nature are not possible because numerous factors always play a role in bringing about an effect. The implications of this state of affairs for the rational design of HIV vaccines are outlined. An alternative approach to obtain useful scientific understanding consists in intervening empirically in the immune system and it is suggested that manipulating the system experimentally is needed to learn to control it and achieve protective immunity by vaccination.